Review article: stem cell therapy in orthopaedic surgery: current status and ethical considerations - Hui, J.H.P.; Azura, M.; Lee, E.H. (2009)
Regenerative medicine using stem cell therapy has sparked much interest in this 21st century not only because of the controversies that surround the ethics involving pluripotent stem cells but their potential for use in the clinic. The ability of stem cells to repair and regenerate new tissues and organs holds tremendous promise for the treatment of many serious diseases and injuries. This review provides a brief summary of the current status of research in stem cells with special emphasis on where we are in terms of the possible clinical application of stem cell therapy in orthopaedic surgery. We look at the available evidence and examine the ethical issues and considerations associated with the clinical use of stem cells.